Proliferation of submerged plants in Laguna Garzón:: causes, consequences and management (INNOTEC, 2024)
Starting in summer 2023, Laguna Garzón registered excessive growth of submerged Myriophyllum quitense plants, covering the entire lagoon, which affected several uses of the system and generated social concern. This work describes the proliferation of aquatic plants, its effects on other biological communities, the environmental conditions that promoted it, and makes recommendations for its management. This species tolerates low to moderate salinities, and this is the first record of a proliferation of this magnitude in the lagoon. Plant cover increased water transparency and nutrients, reduced sediment phosphorus, and generated changes in the benthic community. The proliferation could be due to the high availability of nutrients compared to data from the 2000s and to the prolonged period with freshwater in the lagoon due to the lack of connection to the sea. It is suggested to make artificial openings of the sand bar with sufficient water levels to discharge water, sediments and plants, allowing the entry of marine water that affects plants and cyanobacteria due to their intolerance to high salinities. Mechanical harvesting can be a complementary measure in specific sites. These are measures based on the natural functioning of the system and of low cost.
Keywords: eutrophication; coastal lagoons; Myriophyllum quitense